Inducible regulating homologous recombination enables precise genome editing in Pichia pastoris without perturbing cellular fitness - Bai, Fan; Cai, Peng; Yao, Lun; Shen, Yiwei; Li, Yunxia; Zhou, Yongjin J. (Trends in biotechnology (Regular ed.), 2025)
A tetracycline repressor protein (TetR)/tetO2 inducible system was constructed and optimized in Pichia pastoris.The TetR/tetO2 inducible system dynamically enhanced homologous recombination (HR) for precise editing of multiple genes.Dynamically enhancing HR did not compromise cellular growth or product biosynthesis. The methylotrophic yeast Pichia pastoris (also known as Komagataella pastoris) is an ideal host for producing proteins and natural products. Enhancing homologous recombination (HR) is helpful for improving the precision of genome editing, but results in stress to cellular fitness and is harmful for industrial applications. To overcome these challenges, we developed a tetracycline repressor protein (TetR)/tetO2 inducible system to dynamically regulate the HR-related gene RAD52 in P. pastoris. This approach significantly improved the positivity rate of single gene deletion to 81%. Furthermore, inducible overexpression of endogenous MUS81-MMS4 resulted in high-efficiency (81%) genome assembly of multiple genes. This inducible system had no adverse effect on cell growth in different media and resulted in greater fatty alcohol production from methanol compared with a strain constitutively overexpressing HR-related genes. We anticipate that this inducible regulation is applicable for enhancing HR for precise genome editing in P. pastoris and other non-conventional microbes without compromising cellular fitness. [Display omitted] An anhydrotetracycline (aTc) inducible system was developed to dynamically overexpress homologous recombination-related genes for precise genome engineering in Pichia pastoris. By using this dynamic regulation system, the positive rate of precise gene editing reached 80%, without interrupting cellular growth or fatty alcohol production. An inducible CRISPR-Cas9 gene-editing strategy was constructed in Pichia pastoris, demonstrating excellent homologous recombination (HR) efficiency in genomic integration. This inducible system promoted the positive rates of genome integration of single and multiple genes by up to 80%, without comprising either cellular growth using methanol as a carbon source or fatty alcohol production; in addition, constitutively enhancing HR significantly impaired fatty alcohol biosynthesis. Currently, CRISPR-Cas9 gene-editing tools have successful applications in unconventional yeasts, and enhancement of the HR repair pathway could be a feasible strategy to increase the gene editing efficiency. However, enhancing HR also impacts cellular metabolism and production biosynthesis, effects that would be amplified in large-scale production. Thus, there is an urgent need to coordinate gene-editing efficiency and chemical production. In our study, although the inducible HR system was only performed in P. pastoris and evaluated for fatty alcohol production under shake flask fermentation, it should be evaluated for other products in larger scale biomanufacturing systems, such as bioreactors. Therefore, the current Technology Readiness Level (TRL) of this technology lies between 4 and 5.